Cultural Bases for Self-Evaluation: Seeing Oneself Positively in Different Cultural Contexts. (May 2014) - Becker, Maja; Vignoles, Vivian L.; Owe, Ellinor; Easterbrook, Matthew J.; Brown, Rupert; Smith, Peter B.; Bond, Michael Harris; Regalia, Camillo; Manzi, Claudia; Brambilla, Maria; Aldhafri, Said; González, Roberto; et al.
Several theories propose that self-esteem, or positive self-regard, results from fulfilling the value priorities of one's surrounding culture. Yet, surprisingly little evidence exists for this assertion, and theories differ about whether individuals must personally endorse the value priorities involved. We compared the influence of four bases for self-evaluation (controlling one's life, doing one's duty, benefitting others, achieving social status) among 4, 852 adolescents across 20 cultural samples, using an implicit, within-person measurement technique to avoid cultural response biases. Cross-sectional and longitudinal analyses showed that participants generally derived feelings of self-esteem from all four bases, but especially from those that were most consistent with the value priorities of others in their cultural context. Multilevel analyses confirmed that the bases of positive self-regard are sustained collectively: They are predictably moderated by culturally normative values but show little systematic variation with personally endorsed values.